Gender in the production and sacred spheres of ossetian agricultural culture - Robert P., Kulumbegov (Kavkazologiya, 2022)
The article shows gender differences in the agricultural culture of the Ossetians. Farming, as an important sphere of economic activity, has received wide coverage in ethnographic literature. The everyday life of Ossetians of different sexes, their daily economic practices, and their participa-tion in the religious sphere have been considered in scientific research without considering gen-der. Undeniably, such a generalized approach does not give a full picture of gender differences. The masculine and feminine doctrines were tabooed, defining each gender’s sphere of activity. The participation of mountaineer men and women in economic activity was determined mainly by the physical abilities of the genders, the adaptability of human psychology to a particular work activity. A certain range of labor processes was only in the competence of men, the other - wom-en. There were areas of work allowing gender equality. The men and women participation in the religious sphere was defined by somewhat different criteria. The role of women in sacred rituals was usually determined by well-established stereotypes, based on the notion that women’s role in religious cults was secondary, derived from the predominant role of men. However, the available material shows that women in traditional Ossetian society took an active part in sacred practices. This took place either through the practice of “female” cults or through participation in rituals, through preparing ritual food and drink.